Approximately One Half of Patients Greater Than 40 Years Old Achieve Patient Acceptable Symptomatic State 6 Months After Arthroscopic Partial Meniscectomy - Leslie J. Bisson, M.D; Brett S. Goldstein, C.F.A; Benjamin J. Levy, M.D (Elsevier, 2023)
Purpose: The purposes of this study were to 1) calculate the minimal clinically important difference (MCID) in a population of patients undergoing arthroscopic partial meniscectomy (APM) based on Knee Injury and Osteoarthritis Outcomes Scores (KOOS), 2) quantify the difference between the proportion of patients reaching MCID based on KOOS versus the proportion who considered surgery to be successful based on a "yes" answer to a patient acceptable symptom state (PASS) question, and 3) calculate the percentage of patients experiencing treatment failure (TF). Methods: A large, single-institution clinical database was queried for patients undergoing isolated APM (>40 years of age). Data were collected at regular time intervals, including KOOS and PASS outcome measures. Calculation of MCID using a distribution-based model was performed using preoperative KOOS scores as baseline. Comparison of the proportion of patients surpassing MCID was made to the proportion of patients answering "yes" to a tiered PASS question at 6 months after APM. Proportion of patients experiencing TF was calculated using patients who responded "no" to a PASS question and "yes" to a TF question. Results: Three-hundred and fourteen of 969 patients met inclusion criteria. At 6 months following APM, the percentage of patients meeting or exceeding the MCID for each respective KOOS subscore ranged from 64 to 72% compared to 48% who achieved a PASS (P < .0001 for each subscore). Fourteen percent of patients experienced TF. Conclusions: Six months after APM, approximately one half of the patients achieved a PASS and 15% experienced TF. The difference between achieving MCID based on each of the KOOS subscores and achieving success via PASS ranged from 16% to 24%. Thirty-eight percent of patients undergoing APM did not fit neatly into overt success or failure categorization. Level of Evidence: Level III, retrospective cohort study.